Analysis of Exchange Rate, Inflation, and Benchmark Interest Rate Impacts on the IDX Composite Index Before and After the COVID-19 Pandemic in the Years of 2019-2021 - Shatria, Alifio Ananda; Taufiq, M. (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research examines the impact of inflation, exchange rate, and Bank Indonesia (BI) interest rate on the IDX Composite Index before and during COVID-19. This research's subjects include companies listed on the IDX Composite Index on the Indonesia Stock Exchange (IDX) from 2019 to 2021, spanning a 36-month sample period. This research employs quantitative methods such as multiple linear regression, correlation, multicollinearity, and heteroscedasticity as the classical assumption testing. The coefficient determination test, t-test, and F-test are all part of hypothesis testing. The findings of this research show that inflation and the BI rate have a simultaneous effect due to the influence of the currency rate. All three variables: inflation, currency rate, and BI rate could all have an impact on the IDX Composite Index before and during COVID-19 between 2019 and 2021.